PRINCIPLES OF DEVELOPING STUDENTS’ COMMUNICATIVE COMPETENCE THROUGH TASK-BASED LEARNING - Yakubova Lobar Gulamovna (Scholars Digest Publishing, 2024)
This article explores the principles of developing students' communicative competence through task-based language learning (TBLT). Communicative competence is defined as the ability to use language effectively in real-world situations. TBLT emphasizes the use of tasks that require students to interact and negotiate meaning, promoting the development of all four language skills (reading, writing, listening, and speaking) within a communicative context. The article outlines key principles for effective TBLT implementation, including task selection, planning, scaffolding, feedback, and learner autonomy. It argues that TBLT fosters a student-centered learning environment where students are actively engaged in using language for meaningful purposes.
Keywords: Communicative competence, task-based language learning (TBLT), language skills, student-centered learning.